A "Molecular Water Pipe": A Giant Tubular Cluster Dy72 Exhibits Fast Proton Transport and Slow Magnetic Relaxation - Qin, Lei; Yu, You-Zhu; Liao, Pei-Qin; Xue, Wei; Zheng, Zhiping; Chen, Xiao-Ming; Zheng, Yan-Zhen (Advanced materials (Weinheim), 2016)
A lanthanide cluster, PCC‐72, which is the second largest, with 72 Dy(III) ions assembled into an unprecedented tubular structure, is synthesized. Remarkably, PCC‐72 exhibits superionic proton conductivity (>10−4 S cm−1) under both ambient (with relative humidity RH < 75%) and hot (T > 90 °C, RH = 95%) conditions. Moreover, slow magnetic relaxation is observed, making PCC‐72 the largest Dy(III) cluster that is a single‐molecule magnet.